Psychiatric Morbidity among Child and Adolescent Patients Attending Different Healthcare Settings in Northwest of Dhaka City - Hossain, Md Jahangir; Das, Chayon Kumar (Journal of Monno Medical College, 2023)
Background: A remarkable portion of the child and adolescents were reported suffering from many psychiatric morbidities. Sufferings of this age group have been observed, especially, in the northwest of the capital, including Manikganj. Objectives: This study was carried out to identify psychiatric disorders and correlates in children and adolescents in different clinical settings of Savar and Manikganj. Methodology: This was a descriptive cross-sectional survey among 319 child and adolescent patients, 1-17 years of age, attending five different healthcare settings of Savar and Manikganj. Data were collected from 1st January, 2022 to 31st December, 2022, by a Psychiatrist through face-to-face interview and using a semi-structured questionnaire. Ethical issues to conduct research with human subjects were strictly followed. Results: Among 319 participants with the mean age of 2.73 years, the majority of the participants were from rural area (205, 64.26%) with a monthly family income of 10,001-25,000 BDT (185, 58.00%) and in the age range of >11 years (200, 62.70%). The most common psychiatric problems found were behavioural problem (83, 26.02%), followed by anxiety disorders (41, 12.85%) and intellectual disabilities (50, 15.67%). Parenting problem, family member abroad, familial disharmony, co-morbid disorder, positive family history, study related stress, bullying, death of father, impact of COVID-19, break of study, adjustment issues with sibling were found as risk factors. Conclusions: Majority of the participants had behavioural problem, followed by anxiety disorders and intellectual disability. The results of this study indicate necessity of multi-disciplinary approach to ensure family-based intervention in the treatment of child and adolescent psychiatric patients. Journal of Monno Medical College, June 2023; 9 (1): 30-33